DEVELOPMENT OF A TAKE-HOME EXPERIMENT KIT FOR LIGHT AND OPTICS AS A LEARNING MEDIA OF JUNIOR HIGH SCHOOL STUDENTS - Zulirfan, Zulirfan; Iksan, Zanaton Haji; Mohd. Meerah, Tamby Subahan (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2017)
A take home experiment's kit has been developed in order to help junior high school students to increase their scientific skills and attitudes. Scientific skills that consist of science process skills and manipulative skills, and scientific attitudes of students can be developed only through hands on activity in observing science objects or phenomena and experimenting. By using this simple experiment's kit, students can be able to conduct their home experiments whenever and wherever. What they have done in their experiments and what their experiment's finding will be discuss in classroom with their science teacher. The purpose of this study was to develop light and optical kits that can used by students for conducting science experiment at home. The development of this take home experiment kit has used ADDIE's model, one of the instructional design systems. The steps of this development research were: analysis, design, development, implementation, and evaluation. This take home experiment kit has gone through the stages of expert judgment and practicality testing.